Method of generalization of influence of the parameters of loadings on the characteristics of UHF units (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2007)
The method of generalization of influence of parameters of loadings on the characteristics of UHF units that enables to predict changes of the characteristics at inclusion of UHF units in the radioelectronics systems is given.